MATHEMATICAL MODELLING OF HIV INFECTION - Odundo, Francis; Simwa, Richard; Ongati, Omolo (My University, 2013)
We formulate a deterministic mathematical model for the HIV/AIDS
Keywords: HIV/AIDS; TB; Vertical transmission; Local stability; Global stability